No Easy Answers: Avoiding Potential Pitfalls of De‐implementation. Issue 1 (14th December 2018) - Pinto, Rogério M.; Witte, Susan S.
Abstract: In 2012, the Centers for Disease Control and Prevention (CDC) began to de‐emphasize and de‐implement multiple evidence‐based HIV prevention practices that had been around for 20 years, thus changing the scope of implementation across the globe. The authors provide evidence how existing interventions (e.g., CDC HIV interventions) may influence implementation of interventions that came after the program was discontinued. De‐implementation is an ecological event that influences, and is influenced by, many parts of a system, for instance, implementation of one type of intervention may influence the implementation of other interventions (biomedical and/or behavioral) after a long‐running program is discontinued. Researchers and policy makers ought to consider how de‐implementation of behavioral interventions is influenced by biomedical interventions mass‐produced by companies with lobbying power. The scientific study of de‐implementation will be inadequate without consideration of the political climate that surrounds de‐implementation of certain types of interventions and the promotion of more‐profitable ones. Highlights: Implementation of one type of intervention (behavioral) influences implementation of other types (biomedical) interventions. The surge of biomedical interventions influenced de‐implementation of behavioral interventions. Political climate and community exclusion from implementation decision‐making may lead to early de‐implementation.